IMPLEMENTASI MODEL PEMBELAJARAN BERBASIS ICE BREAKING PADA MATA PELAJARAN BAHASA INDONESIA SMA KELAS XI - Sunaidi, Sunaidi; Harja Susetya, Hemas Haryas (ASMARALOKA: Jurnal Bidang Pendidikan, Linguistik, dan Sastra Indonesia, 2023)
Indonesian is one of the subjects that is effective at all levels of Ice breaking, education, from elementary school (SD), middle school (SMP), high school (SMA), to college. These subjects have different levels of difficulty according to the abilities of each student. The application of ice breaking is also rarely seen from the teachers who teach at Syekh Abdul Qodir Al-jailani High School. Class conditions are also very monotonous and students often sleep when class starts. Therefore, the author aims to research this phenomenon to find out how effective this ice breaking interactive model. From this research, problems were found that were the reason why students were less enthusiastic about participating in the learning process, namely; 1). There are no ice breakers in class. 2). Teachers only use the lecture method in class.